Fortalecimiento de la cadena productiva para la comercialización de la caña de azúcar, del barrio Bono, cantón Atahualpa, provincia de El Oro - Cueva Cueva, Uvita Noemi (2024)
This research is aimed at strengthening the sugar cane production chain in the Bono neighbourhood, Atahualpa Canton, Province of El Oro, which is why the main objective was to design and propose strategies to strengthen the sugar cane production chain by analysing production and marketing, identifying the practices and limiting factors within the sugar cane production and marketing chain in the Bono neighbourhood. The descriptive nature of the research was considered, through the use of deductive, inductive, analytical and synthetic methods with a mixed approach, combining quantitative and qualitative analysis, with a study population of 50 sugar cane producing families, obtaining a sample of 48 producers, to whom direct observation, interview and survey techniques were applied; the information obtained was presented in tables and figures for better understanding and analysis. The results showed that most producers do not implement soil preparation practices prior to planting sugarcane, nor do they have water available for their crops, which has a negative impact on the development of the plantation; pest and disease control is carried out mechanically. On the other hand, cane harvesting is carried out manually with traditional tools. It is concluded that, although there are positive practices, such as the use of organic fertilisers and good seed management, there are also factors that limit the production and commercialisation of sugar cane. The correct analysis and interpretation of the different links in the production chain allowed the construction of strategies aimed at strengthening the sugar cane production chain, which, through their implementation, constitute the main axis for the sustainable development of this area.